2015
DOI: 10.1186/s12887-015-0321-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of foot anthropometry and plantar arch indices between German and Brazilian children

Abstract: BackgroundNowadays, trades and research have become closely related between different countries and anthropometric data are important for the development in global markets. The appropriate use of anthropometry may improve wellbeing, health, comfort and safety especially for footwear design. For children a proper fit of footwear is very important, not constraining foot growth and allowing a normal development. The aim of this study was to compare the anthropometric characteristics of German and Brazilian childr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 15 publications
1
33
0
3
Order By: Relevance
“…≤18 years). From other research, we know that there is a similar comparable development of the medial longitudinal arch in children between cultures and ethnicities 25 . Since we adapted our analysis for possible confounders such as sex, ethnicity, BMI and physical activity, our findings suggest that habitual footwear use influences the development of foot arch morphology in children.…”
Section: Discussionmentioning
confidence: 76%
“…≤18 years). From other research, we know that there is a similar comparable development of the medial longitudinal arch in children between cultures and ethnicities 25 . Since we adapted our analysis for possible confounders such as sex, ethnicity, BMI and physical activity, our findings suggest that habitual footwear use influences the development of foot arch morphology in children.…”
Section: Discussionmentioning
confidence: 76%
“…The Staheli's Plantar Arch Index and Chippaux-Smirak Index (Sacco et al 2015) were calculated (Fig. 1).…”
Section: Methodsmentioning
confidence: 99%
“…Jiménez Ormeno et al (2013) compared the foot morphology of Spanish school children of 6 to 12 years old based on their Body Mass Index and found that significant differences were found between normal weight and overweight children for all variables, except for the arch height. Studies conducted by Sacco et al (2015) showed a higher Chippaux-Smirak index of Brazilian children compared to German children. Abledu et al (2015) obtained bilateral foot prints from Ghanainan students aged between 18-30 years and found footprint dimensions (i.e.…”
Section: Conductedmentioning
confidence: 99%
“…Shoe fit is a complex issue that is influenced by multiple factors. There are differences in the ratio between the length and width of the foot by age [14,15], sex [16] and ethnicity [17][18][19][20], and even within the same sex and ethnicity [21][22][23]. To these factors should be added that the foot is a mobile structure that changes shape during different phases of gait [24], with a flattening of the foot during the mid-stance and elongation of the front of the rearfoot after forefoot contact [25].…”
Section: Introductionmentioning
confidence: 99%